Design, Synthesis, and Biological Evaluation of Novel Hydroxytyrosol Derivatives as Protectors for Vascular Endothelium Against Lipid Overload - Hou XX; Wang S; Ma XX; Wen Y; Li ZJ; Liu XY; Zhang X; Zhang Y; Qin XY (Drug Design, Development and Therapy)
Xi-Xi Hou,1,2,* Shuang Wang,1,3,* Xiao-Xia Ma,1,2,* Ying Wen,1,3,* Zhi-Jun Li,4 Xu-Yun Liu,5 Xing Zhang,3 Yang Zhang,6 Xiang-Yang Qin2 1College of Life Sciences, Northwest University, Xi’an, People’s Republic of China; 2Department of Chemistry, School of Pharmacy, Fourth Military Medical University, Xi’an, People’s Republic of China; 3Department of Recuperation and rehabilitation for flight personnel, School of aerospace medicine, fourth Military Medical University, Xi’an, People’s Republic of China; 4School of Chemistry and Chemical Engineering, Shaanxi University of Science and Technology, Xi’an, People’s Republic of China; 5Center for Mitochondrial Biology and Medicine, the Key Laboratory of Biomedical Information Engineering of Ministry of Education, School of Life Science and Technology, Xi’an Jiao Tong University, Xi’an, People’s Republic of China; 6Department of Medical Electronics, School of Biomedical Engineering, Fourth Military Medical University, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xu-Yun Liu, Center for Mitochondrial Biology and Medicine, the Key Laboratory of Biomedical Information Engineering of Ministry of Education, School of Life Science and Technology, Xi’an Jiao tong University, Xi’an, Shaanxi Province, 710049, People’s Republic of China, Email xuyunliu@xjtu.edu.cn Xiang-Yang Qin, Department of Chemistry, School of Pharmacy, Fourth Military Medical University, Xi’an, Shaanxi Province, 710032, People’s Republic of China, Email qinxiangyang@fmmu.edu.cnBackground and Objective: Hydroxytyrosol (HT) is reported to protect endothelial cells against metabolic overload through inhibiting inflammation. However, the hydrophilic nature of HT limits its oral bioavailability and biological efficiency. The aim of the study was to design and synthesize novel hybrid molecules to improve HT’s biological efficiency.Materials and Methods: A pharmacophore connection strategy was used to design and synthesize novel hybrid molecules by combining HT or its analogues with adamantane (ADM). Palmitic acid (PA) was used to induce lipid overload in HAEC cells, and P407 was used to induce acute hyperlipidemia in C57 mice.Results: We found that DP-ADM, combining ADM and dopamine (a HT analogues), exhibited potent protective effects against metabolic overload-induced endothelial dysfunction. DP-ADM showed low toxicity and inhibited inflammation in response to PA overload in cultured endothelial cells. Additionally, it (30 mg/kg) decreased circulating lipids to an extent similar to HT in a mouse model of hyperlipidemia and was superior to HT in decreasing circulating inflammatory cytokine. It was also superior to HT in improving vascular endothelial function in mice with hyperlipidemia. Mechanistically, DP-ADM inactivated MAPK signaling, as evidenced by downregulated phosphorylation of p38 and Erk. Inhibition of MAPK or NF-κB abolished the anti-inflammatory effect of DP-ADM. Specifically, DP-ADM activated FoxO1 signaling and increased mitochondrial biogenesis in endothelial cells.Conclusion: Overall, DP-ADM is a superior form of HT, highlighting its potential therapeutic use in improving endothelial function in metabolic diseases. Keywords: hydroxytyrosol derivatives, endothelial function, lipid overload, MAPK, inflammation